OBSERVATION PARTICLE SIZE OF MG0.8ZN0.2TIO3 BY LASER DIFFRACTION METHOD - Muhammad Saukani (AL-JAZARI JOURNAL SCIENTIFIC OF MECHANICAL ENGINEERING, 2016)
Observation of particle size in the sample Mg0.8Zn0.2TiO3 (MZT) calcined at 550oC with various holding time 1 hour, 2 hours, 4 hours and 6 hours has been done. The results of X-ray diffraction analysis showed that the formed phase is geikelite (MgTiO3) and rutile (TiO2), which indicates that there had been reaction between Zn and Mg. This research aim to know size distribution of particles in colloidal using laser diffraction method based on principle dynamic light scattering. The average particle diameter measurable each sample ZMT is 310.1 nm, 313.9 nm, 334.2 nm and 365.4 nm which states that the longer the holding time resulted in increase grain size particles.